2023
DOI: 10.1123/ssj.2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Reduce Parental Concern for Concussion Risks in Youth Tackle Football

Abstract: This study sought to identify factors that reduce parental concern of concussion risks for children who play youth tackle American football. Interviews were conducted with parents who allowed children between the ages of 10 and 15 years to play on tackle football teams. Factors that reduced parental concern included advances in equipment safety and helmet technology, active parental monitoring and relationship building with coaches, and social comparisons to other youth athletes regarding their own child’s ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Our data showed parents’ who reported that one of their children had previously experienced a SRC had lower ratings of IRI and ORI, as well as higher SRC knowledge, but no differences in communication intentions. It may have been useful to directly measure parents’ assessment of their own child’s athleticism as previous research has found parents’ social comparisons between their own child’s athleticism to other children reduced their concern regarding their child’s SRC risk (McGlynn et al, 2022). Thus, it is also possible a highly involved parent may perceive their child as being less susceptible to SRCs compared to other children, leading to a decreased motivation to communicate about this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed parents’ who reported that one of their children had previously experienced a SRC had lower ratings of IRI and ORI, as well as higher SRC knowledge, but no differences in communication intentions. It may have been useful to directly measure parents’ assessment of their own child’s athleticism as previous research has found parents’ social comparisons between their own child’s athleticism to other children reduced their concern regarding their child’s SRC risk (McGlynn et al, 2022). Thus, it is also possible a highly involved parent may perceive their child as being less susceptible to SRCs compared to other children, leading to a decreased motivation to communicate about this issue.…”
Section: Discussionmentioning
confidence: 99%